LAMPrimers iQ: New primer design software for loop-mediated isothermal amplification (LAMP) - Akhmetzianova, Liana U.; Davletkulov, Timur M.; Sakhabutdinova, Assol R.; Chemeris, Alexey V.; Gubaydullin, Irek M.; Garafutdinov, Ravil R. (Analytical biochemistry, 2024)
Nucleic acids amplification is a widely used technique utilized for different manipulations with DNA and RNA. Although, polymerase chain reaction (PCR) remains the most popular amplification method, isothermal approaches are gained more attention last decades. Among these, loop-mediated isothermal amplification (LAMP) became an excellent alternative to PCR. LAMP requires an increased number of primers and, therefore, is considered a highly specific amplification reaction compared to PCR. LAMP primers design is still a non-trivial task, and all niceties should be taken into account during their selection. Here, we report on a new program called LAMPrimers iQ destined for high-quality LAMP primers design. LAMPrimers iQ is based on an original algorithm considering rigorous criteria for primers selection. Unlike alternative programs, LAMPrimers iQ can process long DNA or RNA sequences, and completely avoid primers that can form homo- and heterodimers. The quality of the primers designed was checked using SARS-CoV-2 coronavirus RNA as a model target. It was shown that primers selected with LAMPrimers iQ provide higher specificity and reliable detection of viral RNA compared to those obtained by alternative programs. The program is available at https://github.com/Restily/LAMPrimers-iQ.